Green building technologies and materials : selected, peer reviewed papers from the 2011 International Conference on Green Building Technologies and Materials (GBTM 2011), May 30, 2011, Brussels, Belgium - Wu, Xingkuan; Xie, Hao (Advanced materials research ;, 2011)
This book contains selected, peer reviewed papers from the conference on Green Building Technologies and Materials, (GBTM2011), May 30, 2011, Brussels, Belgium. A major goal of this special collection of 47 peer-reviewed papers was to gather together the current knowledge of academic scientists, engineers and industrial researchers and have them share their experiences and research results concerning every aspect of green building technologies and materials, and discuss the practical challenges encountered and the solutions adopted. This is an interesting guide to this increasingly relevant subject. --